UP Diliman Libraries' strategies for combating book theft, mutilation and vandalism - Bañez, Cecilia Poline D.G.; Apolinario, Rhea Rowena U. (Quezon City School of Library and Information Studies, University of the Philippines Diliman, 2017)
Library security has become a common overarching concern among librarians. Different strategies are employed in libraries to prevent or minimize cases of book theft, mutilation and vandalism
The University of the Philippines Diliman campus currently houses 39 degree granting unit libraries. This study sought to determine the different strategies to combat book theft, mutilation and vandalism used by the different degree-granting unit libraries in UP Diliman. It also aims to compare and differentiate the strategies these libraries have and to find out how they are being implemented
All degree-granting unit libraries of UP Diliman, excluding UPDEPP, BML Library and the Institute of Chemistry Library, were the focus of this study. Data gathered from the official inventory records, annual reports, memo and any available documents of each library were interpreted. Interviews with the head librarians and librarians who have institutional memory of the library were also conducted
Majority of the libraries answered Yes when asked if there are still cases of book theft, mutilation and vandalism in their library. Different strategies used by each library are the following: (a) bag counter/lockers, (b) control (checking of bags), (c) security system/gate, (d) CCTVs, (e) availability of online resources, (f) availability of photocopy machines, (g) frequently used materials are located in the reserved area, (h) proper orientation/user education on the rules and regulation of the library, and (i) staff are requested to be more vigilant
Cases of library crimes were minimized after the different strategies were implemented. The security system and CCTVs are the most common strategies that each library employ to be able to combat these crimes. The security system, CCTVs and having a proper orientation on the rules and regulations of the library are the top recommended strategies in order to combat book theft, mutilation and vandalism
Thesis (Bachelor of Library and Information Science)--University of the Philippines Diliman
Keywords: Book thefts; Books -- Mutilation, defacement, etc